Development of an E-Ticketing Information System for the Palembang LRT Based on a Mobile Website - Taufik1 (Institute of Information Technology and Social Science (IITSS), 2024)
The Light Rail Transit (LRT) system in Palembang serves as a major public transportation mode that operates on elevated railways to ensure efficient and modern urban transit. However, the existing ticketing process still relies on cash transactions and member cards, and ticket sales are conducted conventionally without optimal utilization of digital information systems. This approach forces passengers to visit stations physically to purchase tickets and check departure schedules, which is inefficient and time-consuming. This study aims to design and develop an online e-ticketing information system for the Palembang LRT using the System Development Life Cycle (SDLC) methodology. The proposed system enables passengers to book tickets and access real-time departure information through a mobile-based website. The implementation of this e-ticketing system provides greater convenience, reduces queues at ticket counters, and supports the government’s efforts to promote digital transformation in public services.